Indian Jujuba Seed Powder as an Eco-Friendly and a Low-Cost Biosorbent for Removal of Acid Blue 25 from Aqueous Solution - L. Sivarama Krishna; A. Sreenath Reddy; W. Y. Wan Zuhairi; M. R. Taha; A. Varada Reddy (The Scientific World Journal)
Indian jujuba seed powder (IJSP) has been investigated as a low-cost and an eco-friendly biosorbent, prepared for the removal of Acid Blue 25 (AB25) from aqueous solution. The prepared biomaterial was characterized by using FTIR and scanning electron microscopic studies. The effect of operation variables, such as IJSP dosage, contact time, concentration, pH, and temperature on the removal of AB25 was investigated, using batch biosorption technique. Removal efficiency increased with increase of IJSP dosage but decreased with increase of temperature. The equilibrium data were analyzed by the Langmuir and the Freundlich isotherm models. The data fitted well with the Langmuir model with a maximum biosorption capacity of 54.95 mg g−1. The pseudo-second-order kinetics was the best for the biosorption of AB25 by IJSP, with good correlation. Thermodynamic parameters such as standard free energy change (ΔG0), standard enthalpy changes (ΔH0), and standard entropy changes (ΔS0) were analyzed. The removal of AB25 from aqueous solution by IJSP was a spontaneous and exothermic adsorption process. The results suggest that IJSP is a potential low-cost and an eco-friendly biosorbent for the AB25 removal from synthetic AB25 wastewater.